Serum microRNA profiles as prognostic/predictive markers in the multimodality therapy of locally advanced adenocarcinomas of the gastroesophageal junction - Odenthal, Margarete; Hee, Julia; Gockel, Ines; Peters, Leila; Schmitz, Jolly; Stoecklein, Nikolas H.; Driemel, Christiane; Möhlendick, Birte; Schmidt, Thomas; Knoefel, Wolfram T.; Lang, Hauke; Büttner, Reinhard; et al. (International journal of cancer, 2015)
Neoadjuvant multimodality treatment is frequently applied to improve the poor prognosis of locally advanced adenocarcinomas of the gastroesophageal junction. This study aimed to asses if serum microRNA profiles are useable as response indicators in this therapeutic setting. Fifty patients with locally advanced adenocarcinomas of the gastroesophageal junction were included in the study. All patients received neoadjuvant therapy and subsequently underwent surgical resection. Histomorphologic regression was defined as major histopathological response when resected specimens contained less than 10% vital residual tumor cells. Circulating RNA was isolated from pretherapeutic/post-neoadjuvant blood serum samples. RNA from nine patients was applied to PCR microarray analyses Based on these findings possible predictive miRNA markers were validated by quantitative RT-PCR analyses. Depending on the histomorphologic regression, a differential serum microRNA profile was identified by microarray analyses. Based on the divergent miRNA pattern, miR-21, miR-192, miR-222, miR-302c, miR-381 and miR-549 were selected for further validation. During neoadjuvant therapy, there was a significant increase of miR 222 and miR-549. Although on an expanded patient cohort, the six microRNAs could not be validated as markers for therapy response, there was a significant correlation between a high miR-192 and miR-222 expression with a high T-category as well as miR-302c and miR-222 expression significantly correlated with overall survival. Comprehensive miRNA profiling showed a differential microRNA expression pattern depending on the histomorphologic regression in the multimodality therapy of locally advanced adenocarcinomas of the gastroesophageal junction. Moreover, using single RT-PCR analyses a prognostic impact of miR-222 and miR-302c was detected.
Online 27 Nov 2014
Gesehen am 19.06.2020